Viewpoint: Better Late Than Never: Nutrition Education Opportunities for Physicians in the United States - Jaclyn Albin; Dominique R. Williams; John T. Stutts; Giovanna Santander; Andie Lee Gonzalez; Mary Beth Arensberg (Journal of CME, 2024)
Diet and nutrition have an important impact on chronic disease and mortality and have spurred growth in the food is medicine approach. Yet, in the United States (US), post-graduate nutrition education and training for physicians remain limited. This may change as American policies focused on nutrition security, quality care and health equity advance and create new incentives for practicing clinicians to engage in nutrition-focused education and training. This viewpoint summarises why nutrition is essential for quality medical care, nutrition knowledge of US physicians, evolving US policies and advocacy for nutrition in medicine and opportunities for nutrition-focused continuing medical education and training. Clinicians trained in nutrition are important to lead innovation and research in nutrition-focused clinical care and to define best practices and optimise population health.